Uji Kualitas dan Kuantitas DNA Porang (Amorphophallus Muelleri Blume) pada Beberapa Kawasan di Sulawesi Selatan - Abdul Mollah; Muh. Aswad Ashan; Andi Husnul Khatimah (Jurnal Agritechno, 2022)
Porang (Amorphophallus muelleri Blume) is one of tubers biological wealth in Indonesia, but the cultivation of porang plant is still not widely cultivated. One way for increasing the utilization of porang plant is by giving molecular mark in kinship study. Genetic relation of germplasm is very important for breeders because it can be the basis for assembling new individuals with superior characters through the hybridization process in the future. Kinship can be identified based on the similarity of characters with the assumption that different characters are caused by differences in genetic composition. This study used porang leaf samples taken from several agroforestry areas in South Sulawesi, namely Bantaeng Regency, Bulukumba Regency, Gowa Regency, and Maros Regency. Leaf samples were isolated and extracted using liquid nitrogen and DNA measurements were performed using nanodrop spectrophotometry with an absorbance ratio of 260/280. Then purification was carried out using chisam added with NaOAc and isopropanol. The extracted DNA obtained has a fairly good quality because it has a concentration range from 72.9 ng/µl - 1206.9 ng/µl. The lowest score was in MR8 accession and the highest score was in BL11 accession. The results of DNA purification ranged from 5.3 ng/µl - 211.9 ng/µl. The lowest score was in the P.BT-BG13 accession and the highest score was in the P.BL2 accession.